A Boron Difluoride Hydrazone (BODIHY) Polymer Exhibits Aggregation‐Induced Emission. Issue 8 (4th December 2020) - Cappello, Daniela; Watson, Alexander E. R.; Gilroy, Joe B.
Abstract: Polymers that exhibit aggregation‐induced emission (AIE) find use, for example, as cell‐imaging agents and as fluorometric sensors due to their unique optical properties. However, the structural diversity of AIE‐active polymers has not necessarily advanced at the same rate as their applications. In this work, ring‐opening metathesis polymerization is used to synthesize the first example of a polymer (Mn  = 61, 600 g mol −1, Đ  = 1.32) containing boron difluoride hydrazone (BODIHY) heterocycles in its repeating unit. The BODIHY monomer and polymer described absorb and emit in the visible region in solution (λabs  = 428 and 429 nm, λem  = 528 and 526 nm) and as thin films (λabs  = 443 and 440 nm, λem  = 535 and 534 nm). Monomer ( Φ Film  = 10%) and polymer ( Φ Film  = 6%) exhibit enhanced emission as thin films compared to solution ( Φ Soln  ≤ 1%) as well as AIE upon the addition of water to DMF solutions as a result of restriction of intramolecular motion. Enhancement factors for the monomer and polymer are determined to be 58 and 15, respectively. The title BODIHY polymer exhibited an earlier onset of AIE and enhanced sensitivity to solution viscosity when compared to the parent monomer. Abstract : The first example of a polymer containing boron difluoride hydrazones (BODIHYs), prepared by ring‐opening metathesis polymerization, is reported. The BODIHY polymer is emissive as thin films and in the solid state. In solution, the BODIHY polymer exhibits aggregation‐induced emission in DMF solutions containing water and viscosity‐dependent emission properties that differ from those of the parent monomer.